EFEK CITRA MEREK, KEMASAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DI TOKO BUKU GRAMEDIA BATAM - Kartika Kirana Sumirang; Diana Titik Windayati (Zona Manajemen: Program Studi Magister Sains Manajemen Universitas, 2017)
This study was conducted to analyze the brand image, packaging and pricing on purchasing decisions Gramedia bookstore Batam. In this research there are independent variables, which is the brand image, packaging and price, with the dependent variable, the purchase decision. This study is expected to be used to determine the extent of someone's opinion, attractive packaging and economical prices capable of determining consumer purchasing decisions of Gramedia bookstore Batam. Samples taken by researcher were 110 people. Samples were taken with a sampling technique (questionnaire). Data analysis method used is quantitative analysis, validity, reliability test, classic assumption test, multicoloniarity test, heteroscedasticity test, normality test, multiple linear regression analysis, t test, f-test and coefficient of determination R2.